Ambulatory blood pressure monitoring. - Nicholson, W R (1993)
Ambulatory blood pressure monitoring (ABPM) in adults is proving to be useful. The aim of this study was to determine if ABPM is accurate in the lower blood pressure range encountered in children and, equally important, whether it is acceptable to children. Thirty one children, between the ages of 6 and 18 years, were assessed using an ambulatory blood pressure monitor that uses an auscultatory method. Blood pressure was measured in the contralateral arm with a mercury sphygmomanometer and an oscillometric device at the beginning and end of the study for comparison. Over a blood pressure range of 90-130 mm Hg systolic and 40-80 mm Hg diastolic, a close agreement was found with the sphygmomanometer; the limits of agreement (+/- 2 SD) were 11.6 mm Hg for systolic blood pressure and 13.6 mm Hg for diastolic blood pressure. The bias was less than 1.0 mm Hg. The ambulatory device was worn by all patients for at least 16 hours with an average of 52 recordings per patient. The majority found the device comfortable to wear and were not woken from sleep.